Salvinorin A, a kappa-opioid receptor agonist hallucinogen: pharmacology and potential template for novel pharmacotherapeutic agents in neuropsychiatric disorders - Butelman, Eduardo R.; Kreek, Mary Jeanne (Frontiers in Pharmacology, 2015)
Salvinorin A is a potent hallucinogen, isolated from the ethnomedical plant Salvia divinorum. Salvinorin A is a selective high efficacy kappa-opioid receptor (KOPr) agonist, and thus implicates the KOPr system and its endogenous agonist ligands (the dynorphins) in higher functions, including cognition, and perceptual effects. Salvinorin A is the only selective KOPr ligand to be widely available outside research or medical settings, and salvinorin A- containing products have undergone frequent non-medical use. KOPr/dynorphin systems in the brain are known to be powerful counter-modulatory mechanisms to dopaminergic function, which is important in mood and reward engendered by natural and drug reinforcers (including drugs of abuse). KOPr activation (including by salvinorin A) can thus cause aversion and anhedonia in preclinical models. Salvinorin A is also a completely new scaffold for medicinal chemistry approaches, since it is a non-nitrogenous neoclerodane, unlike all other known opioid ligands. Ongoing efforts have the goal of discovering novel semi-synthetic salvinorin analogs with potential KOPr-mediated pharmacotherapeutic effects (including partial agonist or biased agonist effects), with a reduced burden of undesirable effects associated with salvinorin A.